(untitled) (Jurnal Manajemen dan Kewirausahaan, 2013)
Customer Relationship Management (CRM) is one of strategies to retain customers. By maintaining the relationship with customers, hopefully they will be loyal to companies. The objective of this study is to determine the influence of CRM on customer loyalty in JW Marriott Hotel, Surabaya using multiple linear regression analysis. The results of this study show that CRM, including financial benefits, social benefits and structural ties have positive effects significantly on customer loyalty in JW Marriott Hotel Surabaya. The most dominant factor influencing customer loyalty in JW Marriott Hotel, Surabaya is the structural ties.